2022
DOI: 10.3122/jabfm.2022.04.210471
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Uptake of Antiracism Training, Policies, and Practices in Departments of Family Medicine

Abstract: Background: Recent attention and focus on, antiracism training in health care has potential to accelerate our path to social justice and achieve health equity on a national scale. However, theoretical frameworks and empirical data have yet to emerge that explain the uptake of antiracism trainings and their efficacy.Objective: This goal of this study was to test hypotheses regarding uptake of antiracism training in Family Medicine departments using Diffusion of Innovation Theory.Methods: In 2021, we incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A Council of Academic Family Medicine Educational Research Alliance (CERA) study explores antiracism training within academic Departments of Family Medicine as reported by Department Chairs. 10 As we continue to work toward equity in family medicine, studies like this one highlight how much work we have ahead of us. Another CERA study report explores the expansion of point-of-care ultrasound (POCUS) training among faculty in departments of family medicine.…”
Section: Survey Researchmentioning
confidence: 99%
“…A Council of Academic Family Medicine Educational Research Alliance (CERA) study explores antiracism training within academic Departments of Family Medicine as reported by Department Chairs. 10 As we continue to work toward equity in family medicine, studies like this one highlight how much work we have ahead of us. Another CERA study report explores the expansion of point-of-care ultrasound (POCUS) training among faculty in departments of family medicine.…”
Section: Survey Researchmentioning
confidence: 99%
“…To the Editor: In their letter to the editor, Hogans-Mathews et al 1 provide important considerations that expand the scope of the conversation related to our article "Evaluating the Uptake of Antiracism Training, Policies, and Practices in Departments of Family Medicine." 2 In their response, Hogans-Mathews et al highlight advancing the aims of systems of care to include equity as a core outcome. They describe ways to build toward a sustainable foundation of balanced representation among those underrepresented in medicine (URiM) with partnered allyship from non-URiM colleagues.…”
mentioning
confidence: 99%
“…To the Editor: We were pleased to read the article entitled, "Evaluating the Uptake of Antiracism Training, Policies, and Practices in Departments of Family Medicine" by Sanders et al, which focuses on the use of Diffusion of Innovation Theory to evaluate antiracism trainings in departments of Family Medicine (FM). 1 We applaud this much needed evaluation of FM departments and their current practices with antiracism trainings, policies, and implementation uptake and efficacy. We also agreed with the need to promote equity in health and social justice with multiple interventions including antiracism training.…”
mentioning
confidence: 99%
“…We also agreed with the need to promote equity in health and social justice with multiple interventions including antiracism training. 1 The promotion of equity and diversity are of utmost importance in medicine. A more recent proposal to the Quadruple Aim, coined the Quintuple Aim, adds a fifth aim: advancing health equity.…”
mentioning
confidence: 99%
See 1 more Smart Citation